2015
DOI: 10.18632/oncotarget.5896
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ageing-associated naturally occurring peptides in human urine

Abstract: To assess normal and pathological peptidomic changes that may lead to an improved understanding of molecular mechanisms underlying ageing, urinary peptidomes of 1227 healthy and 10333 diseased individuals between 20 and 86 years of age were investigated. The diseases thereby comprised diabetes mellitus, renal and cardiovascular diseases. Using age as a continuous variable, 116 peptides were identified that significantly (p < 0.05; |ρ|≥0.2) correlated with age in the healthy cohort. The same approach was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 45 publications
1
41
1
Order By: Relevance
“…Considering that the group of normal subjects was much younger (mean of age 30) than the cancer groups (means of age ranging between 61 to 68 years), we investigated further if the differences in O‐glycopeptide and N‐glycopeptide abundance may be related to age. Investigation of previous data on the association of urinary peptides with age in over 10 000 subjects revealed no significant association of any of the O‐glycopeptides and N‐glycopeptides with age. We further extracted data from an additional group of older, apparently healthy subjects ( n = 226, mean of age 60, similar to the age range of the cancer groups).…”
Section: Resultsmentioning
confidence: 72%
“…Considering that the group of normal subjects was much younger (mean of age 30) than the cancer groups (means of age ranging between 61 to 68 years), we investigated further if the differences in O‐glycopeptide and N‐glycopeptide abundance may be related to age. Investigation of previous data on the association of urinary peptides with age in over 10 000 subjects revealed no significant association of any of the O‐glycopeptides and N‐glycopeptides with age. We further extracted data from an additional group of older, apparently healthy subjects ( n = 226, mean of age 60, similar to the age range of the cancer groups).…”
Section: Resultsmentioning
confidence: 72%
“…A top‐down CE‐MS to discover disease biomarkers in biofluids has also been described . The arrangement of the equipment is simple.…”
Section: Applicationsmentioning
confidence: 99%
“…More recently, urinary proteomes of 1227 healthy and 10 333 diseased individuals between 20–86 years of age were investigated . A total of 116 peptide biomarkers were identified that significantly correlated with age in the healthy cohort.…”
Section: Proteomic Classifier Scores Cut‐off Values For Cad238 and Cmentioning
confidence: 99%